Matrix mechanical plasticity regulates cancer cell migration through confining microenvironments. Issue 1 (December 2018) - Wisdom, Katrina; Adebowale, Kolade; Chang, Julie; Lee, Joanna; Nam, Sungmin; Desai, Rajiv; Rossen, Ninna; Rafat, Marjan; West, Robert; Hodgson, Louis; Chaudhuri, Ovijit
Abstract Studies of cancer cell migration have found two modes: one that is protease-independent, requiring micron-sized pores or channels for cells to squeeze through, and one that is protease-dependent, relevant for confining nanoporous matrices such as basement membranes (BMs). However, many extracellular matrices exhibit viscoelasticity and mechanical plasticity, irreversibly deforming in response to force, so that pore size may be malleable. Here we report the impact of matrix plasticity on migration. We develop nanoporous and BM ligand-presenting interpenetrating network (IPN) hydrogels in which plasticity could be modulated independent of stiffness. Strikingly, cells in high plasticity IPNs carry out protease-independent migration through the IPNs. Mechanistically, cells in high plasticity IPNs extend invadopodia protrusions to mechanically and plastically open up micron-sized channels and then migrate through them. These findings uncover a new mode of protease-independent migration, in which cells can migrate through confining matrix if it exhibits sufficient mechanical plasticity. In order to metastasize, cancer cells must migrate through basement membranes and dense stroma, and proteases are thought to be required due to the confining nature of these matrices. Here the authors use synthetic matrices to show that cells can migrate through confining matrices using force generation alone, rather than protease degradation, if the matrices exhibit mechanical plasticity.